Interdependence of Economic Value Added, Net Present Value and Market Value of a Company - Милорад Иванишевић (Acta Economica, 2015)
Economic value added as a method for company performance measurement for time periods of one year is firstly analyzed in the paper. After that we discuss market value added as a diﬀerence between company market value and value of invested capital. Then the interdependence between economic value added and market value added is explained. Finally, we point out that there is relationship between net present value as a method for investment rentability evaluation and company market value.